Detecting patterns in the behaviour of goalkeepers and kickers in the penalty shootout: a between-gender comparison among score situations. Issue 2 (4th March 2023) - Avugos, Simcha; Azar, Ofer H.; Sher, Eran; Gavish, Nadav; Bar-Eli, Michael
ABSTRACT: There is plenty of research on penalty kicking in men's soccer, with a focus on either the goalkeeper or the penalty taker. Yet women's soccer and their playing behaviour are under-represented in research. The current study was designed to examine gender differences in the choice patterns of expert kickers and goalkeepers during penalty shooting in relation to the previously documented right-oriented bias. Using videos of penalties from shootouts at the highest level of men's and women's international soccer, we recorded the goalkeeper's dive direction and accurately measured the location of the ball as it crossed the goal line. We created a map of all kicks and their outcomes (goal, no goal, off-target). Our mapping procedure allowed us to use alternative definitions for the goal centre width and to extract the corresponding kick distribution between right, centre and left. In addition to analysing the potential right-oriented bias in women goalies' behaviour, we also analysed the joint distribution of kickers' and goalkeepers' choices for each score situation (behind, tied, or ahead). Our findings indicate that the goalkeepers' general tendency was to dive more often to the right, while the kickers' tendency was to shoot to the right of the goalies. Moreover, this latter tendency of kicking to the goalies' right was found to be stronger among the female kickers. Finally, our analysis refutes the claim that goalkeepers exhibit a detrimental right-oriented bias, with this conclusion being even stronger among female goalies.